THU0291 Endothelial Progenitor Cells in Systemic Lupus Erythematosus: Effect of B Lymphocyte Stimulator and Its Inhibition. (15th July 2016) - Spinelli, F.R.; Barbati, C.; Massaro, L.; Ceccarelli, F.; Miranda, F.; Truglia, S.; Alessandri, C.; Conti, F.; Valesini, G.
Abstract : Background: Cardiovascualar disease is the main comorbidity in Systemic Lupus Erythematosus (SLE). Circulating endothelial progenitor cells (EPCs) are bone marrow-derived cells, able to differentiate into mature endothelial cells. Several studies demonstrated a reduction and functional impairment of EPCs in SLE patients, contributing to the endothelial dysfunction characterizing these patients. Belimumab (BLM), a human monoclonal antibody anti-B Lymphocyte Stimulator (BLyS) is the first biological drug approved for the treatment of SLE patients. In murine models of atherosclerosis, treatment with a BLyS inhibitor slowed the progression and reduced the size of atherosclerotic plaque. Objectives: to evaluate the effect of BLyS inhibition on EPCs both ex vivo – in SLE patients receiving BLM– and in vitro . Methods: We enrolled consecutive patients with SLE diagnosed according to 1997 ACR criteria. Patients with known cardiovascular disease were excluded. As control, we studied age and sex-matched healthy subjects. SLE disease activity was evaluated by SLEDAI 2K at baseline and after 4 and 12 weeks of BLM; blood samples were collected at the same time-point. Peripheral blood mononuclear cells (PBMC) isolated by Ficoll density-gradient centrifugation were incubated with fluorescein isothiocyanate-labeled anti-CD34 monoclonal antibodies and phycoerythrin-labeled anti VEGF-R2/KDR; acquisition was performed by flow cytometry: EPCs were defined as CD34/KDR double-positive cells. For in vitro studies, recovered cells isolated from healthy donors' PBMC were plated on dishes coated with human fibronectin. Apoptosis was investigated after 6, 12, 24 and 48 hours of incubation with BLyS at different concentration – 5, 20 and 100 ng/ml – and re-evaluated after 6 hours of co-incubation with BLM at 173 and 300 μg/ml. Kolmogorov-Smirnov showed the normal distribution of EPCs; data were expressed as mean±standard deviation. To test the hypothesis that BLM may increase EPCs number we used one-tailed T-test. A p value <0.05 was considered statistically significant. Results: We enrolled 18 female patients (mean age 41.3±10.1 yrs, mean disease duration 19.2±9.2 yrs). Number of EPCs was significantly lower in SLE patients compared to NHS (p<0.0001). Of the 18 patients, 10 (mean age 44.9±9.6 yrs, mean disease duration 15.6±10.0 yrs) started BLM for refractory disease (mean baseline SLEDAI 2K 7.1±3.1). After 4 and 12 weeks, SLEDAI 2K tended to decrease (p=ns). Baseline EPC number was significantly lower compared to NHS (p=0.002). After 4 weeks, mean EPC number increased to 0.026±0.015 (p=0.038 vs baseline; p=n.s. vs NHS). At week 12 we observed a slight decrease of EPC number compared to week 4 (0.021±0.015 p=ns). In vitro studies demonstrated that 20 ng/ml of BLyS induced apoptosis of EPC after 6 hours of incubation; this effect was reverted by the addiction of 173 and 300 μg/ml of BLM. BLM alone did not induce apoptosis of EPC. Conclusions: This study confirms a reduction of EPCs number in SLE patients compared to NHS. Treatment with BLM significantly increased EPCs number. In vitro data suggest a direct role of BLM by demonstrating a pro-apoptotic effect of BLyS that was reverted by the addition of the human anti-BLyS in EPCs culture. These results furhter support a contribution of BLyS and B cells in the promotion of atherosclerosis. Disclosure of Interest: None declared